Testosterone Is Protective in the Sexually Dimorphic Development of Arthritis and Lung Disease in SKG Mice. Issue 6 (30th May 2013) - Keith, Rebecca C.; Sokolove, Jeremy; Edelman, Benjamin L.; Lahey, Lauren; Redente, Elizabeth F.; Holers, V. Michael; Sakaguchi, Shimon; Robinson, William H.; Riches, David W. H.
<x xml:space="preserve">Abstract</x> Objective Rheumatoid arthritis (RA) is a sexually dimorphic inflammatory autoimmune disease with both articular and extraarticular disease manifestations, including RA‐associated interstitial lung disease. Low levels of testosterone have been linked to disease severity in men with RA, and supplemental testosterone has been shown to improve RA symptoms in both postmenopausal women and men with low levels of testosterone. The mechanisms by which sex and sex steroids affect the immune system and autoimmunity are poorly understood. The purpose of this study was to examine the protective effects of testicular‐derived sex hormones on the development of joint and lung disease in an autoimmune mouse model. Methods Arthritis prevalence and severity were assessed in orchiectomized, sham‐orchiectomized, and intact male SKG mice as well as in female SKG mice over a 12‐week period after intraperitoneal injection of zymosan. Lung tissues were evaluated by quantifying cellular accumulation in bronchoalveolar lavage fluid, collagen levels, and histologic changes. An antigen microarray was used to evaluate autoantibody generation under each experimental condition. Results Female SKG mice developed arthritis and lung disease at increased prevalence and severity as compared to intact male mice. The absence of testosterone after orchiectomy led to increased arthritis, lung disease, and autoantibody generation in orchiectomized male mice as compared to intact male mice. Conclusion SKG mice represent an authentic sexually dimorphic mouse model of both the joint and lung disease seen in humans with RA. Testosterone protects against the development of joint and lung disease in male SKG mice.